Latin America in the 21st Century: Regional Development Trajectories - D. A. Kuznetsov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Latin America and the Caribbean region (LAC), which includes more than thirty countries, is traditionally characterized by a complex combination of elements of homogeneity and heterogeneity. The latter, stemming from traditional economic social and political diﬀerentiation and ideological polarization, in the modern context strengthens regional contradictions and creates new division lines. At the same time, the turn of the 20th and 21st centuries was marked by a growing integration of the region into the global market and globalization processes in general. In order to provide an outlook on the possible future developments in LAC, the author examines how the key trends of the current world politics permeate the region. The theoretical framework of the paper is based on the methodology proposed by the Russian researcher M.M. Lebedeva who outlines three basic megatrends — globalization, integration, and democratization and their counter-trends — deglobalization, disintegration, and dedemocratization, accordingly. It is within this broader context of a complex interplay of these trends and counter-trends, that the dynamics of regional processes in LAC is conceived. On this basis, the author identiﬁes three possible regional development scenarios. The ﬁrst one presupposes strengthening of institutional linkages between North, Central, and South America on the basis of Pan-American ideas. The second implies civilizational ‘isolation’ of LAC within large but still only regional integration projects. Finally, the third scenario proceeds from the linear development of the current regional trends. It implies further fragmentation of LAC within subregional organizations and chaotization of regional international relations. The author concludes that currently the regional development is aﬀected predominantly by counter-trends, which are evidenced by increasing isolationism, an impasse facing major integration projects and democratic institutions, and the growth of populist movements. At the same time, all this shows that Latin America is fully integrated in global economic and political processes since these counter-trends characterize the development of a contemporary system of international relations in general.